The life and times of post-modernity - Tester, Keith, 1960- (Routledge, 1993)
This critical review of 'postmodernity' argues that we are not living in the midst of a new 'great transformation'. Rather, the problems and possibilities of contemporary culture reflect the paradoxes and dreams of modernity.